Controlling Gas Selectivity in Molecular Porous Liquids by Tuning the Cage Window Size. Issue 19 (12th March 2020) - Egleston, Benjamin D.; Luzyanin, Konstantin V.; Brand, Michael C.; Clowes, Rob; Briggs, Michael E.; Greenaway, Rebecca L.; Cooper, Andrew I.
Abstract: Control of pore window size is the standard approach for tuning gas selectivity in porous solids. Here, we present the first example where this is translated into a molecular porous liquid formed from organic cage molecules. Reduction of the cage window size by chemical synthesis switches the selectivity from Xe‐selective to CH4 ‐selective, which is understood using 129 Xe, 1 H, and pulsed‐field gradient NMR spectroscopy. Abstract : Control of pore window size : Narrowing the windows of the organic cage used to form molecular porous liquids leads to tuning of the gas selectivity. Pulsed‐field gradient NMR spectroscopy is used to understand the selectivity.